Hjalmar Schacht, Sang Diktator Perekonomian Jerman (Sebuah Tinjauan Historis) - Daniel Ramadhan; Wawan Darmawan; Achmad Iriyadi (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2017)
This article is the result of the research that discusses about the role of Hjalmar Schacht in building the German economy in 1933-1939. The main problem that is studied in this article is "How was the role of Hjalmar Schacht in order to built the German economy in the period 1933-1939?". The method used in this study is historical method consisting of four steps of activity, there are; heuristics, source criticism, interpretation, and historiography. Based on research studies that have been done, Hjalmar Schacht had a very important role in the development of the German economy after World War I. In order to rebuild the German economy, Schacht issued many policies, among others; (1) Addressing the problems of unemployment, (2) Funding of German industries, and (3) Addressing the needs of industrial raw materials. However, these policies were issued not only to improve the German economy, but it was planned to rearm the German military in preparation for a larger war in 1939.